Optimization of Kring Serse Activities in Preventing Criminal Acts of Theft of Two-Wheel Motorized Vehicles in the Jurisdiction of the Blitar City Police - Yudhistira, La Ode Ananta (Indonesian Journal of Police Studies, 2024)
In the Blitar City Police Legal Area, motor vehicle theft crimes (also known as criminal anarchy) are investigated in this honors thesis through the use of standby patrol activities. Standby patrol is an appellation used to describe the strict, regular, and systematic schedule that the Blitar City Police use to keep an eye out for criminal activity. Nonetheless, the factual circumstances that arise in the field frequently offer proof that criminals nevertheless remain successful in committing their crimes. This qualitative study employs the ethnomethodological paradigm in which requiring borrowing sociological implications from case studies to explain why the core of the issue can arise in these factual circumstances. This can be done through either in-depth interviews or participant observation. The following participants are included in this study, which was established between October and December of 2023: perpetrators, victims (the society), and personnel of the Blitar City Police Detective Unit. The aforementioned investigation culminates with two findings. First, in-depth interviews and secondary data revealed that the growing number of theft cases throughout the 2021–2022 interval served as the driving force behind this investigation. Fake keys and abandoned keys sum up the bulk of cases' modus operandi, or frequent habit. It is visible from early in the morning until first light. Second, there are ethnometodological flaws in the management theory framework of the 6M concept in a number of ways, as observed in the field, i.e. (1) man, or a scant number of employees resulting to an an assortment of tasks; (2) money, or inadequate budget to enable employees to fulfill their daily obligations; (3) method, or practice combined with minimal briefings and debriefings, resulting in the execution of standard procedural without clear objective commandment; and (4) market, or the absence of cooperation amongst functional units. These four factors are the main cause of the issue that makes the stanby patrol that the Blitar City Police conducts unanticipated. Thus far, unit members have been able to compensate for these shortcomings by virtue of their proficiency or ability to finish everyday mission with the help of community cooperation (machine, WhatsApp private network technologies). As a result, this study offers further insights in the manner of recommendations derived from mentioned issues.